Kajian Validasi Data Global Satellite Mapping of Precipitation (GSMaP) di Bengkulu - Diana Cahaya Siregar; Nasyithah Az-Zahra Lubis; Abdi Jihad; Tuti Herawati (Jurnal Fisika dan Aplikasinya, 2020)
The rainfall observation data is hard then we need other option to obtain the data which is easier and more accurate. One of methods to obtain rainfall data is using remote sensing. GSMaP is one among products produces by remote sensing which is able to obtaining rainfall data using satellite. The aim of this study is to validate the rainfall data using GSMaP to the rainfall observation data in Bengkulu for 2012-2015. The method used is processing GSMaP data into monthly data then comparing it with in situ data. In addition, there's processing data with statistical test. Based on the results, the correlation between GSMaP data and observation data is in range of 0,4 to 0,89. It shows that GSMaP data is quite valid to be used to fill incomplete rainfall data in Bengkulu, but it has not been able to intrepret value close to underforecast data.